The Network Society Revisited. (June 2023) - Castells, Manuel
The theory of the network society, in my own version, was originally elaborated in the book that, under the title The Rise of the Network Society, I published in 1996. It was revised and updated in the 2000 and 2010 editions. However, the significant social change that has taken place on a global scale in the last decade provides an opportunity to reassess its heuristic value. Therefore, in this text, I will attempt to consider the currency of the theory of the network society when confronted with these changes.